International Organizations on Fighting against Corruption: Legal Means and Methods of their Implementation in National Legal Systems - KLYUKOVSKAYA, Irina Nikolayevna; GALSTYAN, Inessa Shagenovna; LAUTA, Oleg Nikolayevich; MAYBORODA, Elvira Tagirovna; CHERKASHIN, Evgeniy Yurievich (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The urgency of the article is stipulated by the importance to form international legal institutes aiming at fighting against corruption and the problem related to implementing international regulations of the anti-corruption purposefulness in national legal systems. The goal and tasks of the article are based on the analysis of general principles, tasks and tools applied by international organizations when fighting against corruption to define problems and perspectives of their implementation in national legal systems. The use of formal legal methods allowed to research the following groups of the most important anti-corruption regulators: international anti-corruption standards and principles, international and legal mechanisms of monitoring the fulfillment of anti-corruption conventions, and international legal measures to prevent corruption. The use of comparative legal approach and methods of legal comparativistics, which are included in it, allowed to correlate international anti-corruption conventions adopted both under the guidance of the international universal organization – United Nations Organization, and on the level of a number of international regional organizations: the Council of Europe and the European Union. The research revealed that the diversity of forms of international organizations fighting against corruption was stipulated by the differentiation of solutions whose development was supposed as a result of the statutory activity of international organizations. The Organization of United Nations holds a special place here. It considers the fight against corruption as one of the elements to provide stability of the world order. The opposition of corruption in this term is considered as an interrelated element stipulated by the commonness of interests of all developed states. Empiric data show that the lack of the system counteraction to corruption as a negative social and legal phenomenon causes the erosion of legal institutes, and finally, their full non-operability. Social and legal institutes that are available on the regulatory basis but that actually do not work are an element of its constant destabilization. It is necessary to further integrate international cooperation in this area. It must result in the formation of the standard unanimity of institutes of national jurisdiction in fighting against corruption.